AIN to PIN transfer for PIN palsy following distal biceps tendon repair: a case report. Issue 1 (31st December 2022) - Fairley, Jillian A.; Daneshvar, Parham
Abstract: Posterior interosseous nerve injury after distal biceps repair significantly impairs hand function. For treatment, we describe an anterior interosseous nerve to posterior interosseous nerve transfer. Our technique is useful when the injury is too distal for median nerve transfer or when the zone of injury is too long for nerve graft reconstruction.